2020
DOI: 10.1111/csp2.152
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes to assess population connectivity in the declining European Turtle Dove (Streptopelia turtur)

Abstract: European Turtle Doves (Streptopelia turtur) are long-distance migrants and have experienced a population decline of more than 78% since 1980. Their conservation depends on refined knowledge of breeding origins and population connectivity. Feathers collected at stopover sites, but molted at breeding grounds, provide an opportunity to assign birds to potential regions of origin using tissue stable hydrogen isotope values and relate those to a European feather hydrogen isoscape. Here, 101 feather samples from 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Animals have evolved the capacity to migrate vast distances in response to changing environmental conditions (Dingle and Drake 2007, Chapman et al 2011, Milner‐Gulland et al 2011). While migratory behavior is well‐recognized among vertebrates like birds and mammals (Lehnert et al 2018, Marx et al 2020), much less is understood about invertebrate migration. Recent evidence has revealed mass seasonal movements of insect biomass to be among the largest terrestrial animal migrations on Earth (Hu et al 2016), a phenomenon which has major ecological and economic ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…Animals have evolved the capacity to migrate vast distances in response to changing environmental conditions (Dingle and Drake 2007, Chapman et al 2011, Milner‐Gulland et al 2011). While migratory behavior is well‐recognized among vertebrates like birds and mammals (Lehnert et al 2018, Marx et al 2020), much less is understood about invertebrate migration. Recent evidence has revealed mass seasonal movements of insect biomass to be among the largest terrestrial animal migrations on Earth (Hu et al 2016), a phenomenon which has major ecological and economic ramifications.…”
Section: Introductionmentioning
confidence: 99%
“…Another study that investigated breeding ground provenance of migrating turtle doves, including some of the sampled individuals from this study, showed relatively coarse and broad possible distribution ranges using δ 2 H f only, and no spatially precise breeding localities could be assigned (Marx et al 2020). Therefore, a precise estimation of the connectivity between breeding and wintering areas was not possible in this study, as we do not know the exact breeding areas of individuals sampled during migration.…”
Section: Differences In δ 2 H F and δ 13 C F Valuesmentioning
confidence: 84%
“…The low probability of recapturing banded individuals and recent technological advances triggered the development of new approaches (Bächler et al, 2010; Webster et al, 2002). Among them, stable isotopes have been applied in a growing number of migration studies (Alisauskas & Hobson, 1993; Chamberlain et al, 1997; Hobson et al, 2004; Hobson, Keith, Van Wilgenburg, Wassenaar, & Larson, 2012; Hobson, Keith, Van Wilgenburg, Wassenaar, Powell et al, 2012; Marx et al, 2020; Phillips et al, 2009). The isotopic signature of feather keratin is representative for the place of moult and it is preserved unaltered for centuries (Hobson & Wassenaar, 1997; Navarro et al, 2020).…”
Section: Introductionmentioning
confidence: 99%